The Effect of Managerial Competence and Interpersonal Communication on the Performance of Heads of SMKNegeri in Palembang City - Lenny Widiawati; Yasir Arafat; Heri Setiyo Nugroho (International Journal of Educational Technology and Society, 2025)
Education has an important role in improving the quality of life of society as a whole, through good education, it can improve welfare, increase awareness about the importance of health, environment, and security, and increase the ability to contribute to society (Santoso, Karim, & Maftuh, 2023). Education not only means teaching about reading and writing, but it also provides the knowledge, skills, and values necessary to live in society. Education plays a key role in helping individuals reach their potential (Nurnaningsih, Norrahman, & Wibowo, 2023).